“Implementación de una aplicación para el reconocimiento de patrones de diseño mediante una red neuronal artificial multicapa en el centro de propaganda y comunicación social de la Universidad Técnica de Cotopaxi Extensión La Maná.”. - Ayala Tigasi, Ginson Steven (2021)
The purpose of this project is to facilitate the storage of advertising images of the Technical University of Cotopaxi La Maná Extension and to identify more efficiently the similarity between advertisements, through the implementation of an application for the recognition of design patterns through a multilayer artificial neural network in the Promotion and Social Communication Center. This application seeks to shorten the time and cost in the recognition of advertisements to avoid redundancy and falsification, work that currently corresponds to the group in charge of the propaganda of commemorative dates of the University, it will help to have a place to store all advertising projects and not depend on other external pages or social networks. For the development of the system, the corresponding information gathering was carried out with the people close to the problem, to obtain the most necessary functional and non-functional requirements, which made the application be divided into access block, new information entry block and pattern recognition code execution block design with percentage variation, using the SCRUM methodology, more in line with the current situation, to bring a systematic and agile order in the development of the project, with the interface design, coding, testing and implementation, Netbeans programming language was used, Java and MySQL as database management system, tools with a minimum cost and adapted to the requirements of the application, resulting in the Promotion and Social Communication Center of UTC La Maná will enjoy the ease of implementation and use with appropriate security to take care of the interests of this area.